Perancangan Aplikasi Smart Desa Mobile Pada Desa Pasarawa Dengan Metode Waterfall - Anas Fauzan (Institut Teknologi dan Bisnis Indonesia, 2025)
This research aims to design a mobile-based Smart Village application to be implemented in Pasarawa Village. By employing the Waterfall method, the development process of this application is conducted systematically through the stages of analysis, design, implementation, testing, and maintenance. The application is designed to enhance the efficiency of public services and facilitate communication between the village government and its residents. Features developed include village activity information, administrative services, and a complaint system. The results of this design are expected to provide significant benefits for village management and improve community involvement in the village development process.